Analysis of the Basic Mandarin Learning Needs at Junior High School in Makassar - Azizah, Mir'ah (Wen Chuang:Journal of Foreign Language Studies, Linguistics, Education, Literatures, Cultures, and Sinology, 2024)
This study aims to analyse the needs for basic Mandarin language learning at Frater Junior High School Makassar, as a reference to determine whether this activity should be continued, as well as to aid in the development of teaching materials and syllabus creation. This research identifies the challenges in learning Mandarin after participating in Mandarin language classes, the benefits of learning Mandarin, the sustainability of the basic Mandarin training program, and the need for basic Mandarin language learning based on the four fundamental language skills.The research uses a descriptive analysis method with a quantitative approach. Data was collected through the distribution of questionnaires to 15 respondents, including students from Frater Junior High School Makassar, teachers, and parents. Analysis of the questionnaire data shows that 53.3% of respondents are interested in learning Mandarin by increasing the number of hours of study and changing the theme of the material, as they feel they already understand the current themes provided. Regarding the introduction and writing of Hanzi, they experience difficulty, with 93.3% of participants reporting that they find it hard to learn Hanzi.The analysis of the basic Mandarin language learning needs concludes that students require Mandarin to understand simple conversations and vocabulary. Keyword: Needs analysis, Mandarin, Learning